Outcome of Flexible Nail in The Management of Open Humerus Fracture - Khan, Sifat Ullah; Naeem Ullah (Indus Journal of Bioscience Research, 2025)
Background: Open humeral shaft fractures have significant challenges in orthopedic surgery, particularly regarding its union outcomes. Flexible intramedullary nailing offers a good solution, but evidence on its effectiveness in open fractures remains limited in area like Peshawar, especially in terms of union rates and associated patient factors. Objective: To determine the frequency of outcomes with flexible nail in patients with open humerus fracture. Study Design: Descriptive cross-sectional study. Duration and Place of Study: The study was conducted from September 2024 to February 2025 at the Department of Orthopedic Surgery, Lady Reading Hospital, Peshawar. Methodology: A total of 115 patients aged 18–60 years with open humeral shaft fractures were enrolled. All patients underwent fixation with titanium elastic nails via a retrograde approach. Follow-up evaluations were conducted at one, two, and three months postoperatively to assess union outcomes. Complete union was defined radiographically within two months, delayed union by the third month, and non-union as failure to show bridging callus at three months. Results: Of the 115 patients, 91 (79.1%) achieved complete union, 12 (10.4%) experienced delayed union, and 12 (10.4%) developed non-union. Male patients comprised 80.9% of the cohort. A significant association was observed between BMI and union outcome (p=0.007), with higher BMI linked to increased non-union rates. Socioeconomic status (p=0.019) and ASA grade (p<0.001) also showed significant associations, while age, gender, and residence did not reach statistical significance. Conclusion: Flexible intramedullary nailing is an effective treatment for open humeral shaft fractures, with a high rate of complete union.